Anguilla anguilla - Çiçek, Erdoğan; Fricke, Ronald; Sungur, Sevil; Çapar, Osman Bahadir; Golani, Daniel (Zenodo, 2023)
Anguilla anguilla (Linnaeus, 1758) [N]—European eel; Tzlofach eyropi or europi Taxonomy. Original description: Muraena anguilla Linnaeus, 1758: 245 [Europe, Mediterranean Sea, Baltic Sea, northeastern Atlantic (original: “in Europa; maxima in lacu Cornachio Ferrariensi”); localities include Sweden; England; Belgium; Germany; Poland; France; Ferrara and Rome, Italy; Lesbos Island, Greece; Syria; no types known].—Israel synonyms: None.—Revisions: Ege (1939: 90).—Illustration: Kottelat & Freyhof (2007: 62, fig.). Status in Israel. First record from Israel by Lortet (1883: 179) and Tristram (1884: 177) as Anguilla vulgaris , and Spicer (1931); confirmed by Goren & Ortal (1999: 4).—Israel material: HUJ. Distribution and habitat. Distribution in Israel: Mediterranean watersheds.—Distribution in River Basin: 1- Western Basin, 2-Dead Sea Basin.—General distribution: Western Atlantic: larvae in Sargasso Sea and Gulf Stream; eastern Atlantic, Baltic Sea, North Sea, White Sea, Mediterranean Sea, Sea of Marmara, Black Sea: European seas and adjacent watersheds, spawning and larval migration routes to and from the western Atlantic. Introduced in the Caspian Sea basin.—Distribution in Ecoregion: 436-Coastal Levant, 438- Jordan River.—Habitat: This species is catadromous and found in a range of habitats, from small streams to large rivers and lakes, and in estuaries, lagoons, and coastal waters. It also occupies open ocean areas during migrations but is rarely observed in this habitat. Under natural conditions, it only occurs in bodies of water that are connected to the sea; it is stocked elsewhere. Freshwater, brackish, marine. Economic importance. Commercially important. Conservation. Conservation Status in Israel: Unknown.—IUCN: CR (IUCN 2023).—Threats: ABS, FIT, HAB, EUT, CON, COM, TOU.—Moderate sensitivity to human activities.—Keystone species.—Decline status: Decreasing.—Moderate priority for conservation action. Remarks. This species has been stocked, unintentionlly, in the Lake of Galilee together with mugilids ...